Magnetic structure of subsurface layers of single crystalline yttrium-iron garnet films implanted with Si+ ions with various energies - Pylypiv, V.M.; Garpul, О.Z.; Kotsyubynsky, V.O.; Ostafiychuk, B.K.; Mokliak, V.V.; Kopcewicz, M.; Syvorotka, І.І. (Физическая инженерия поверхности, 2012)
Findings from the investigation of subsurface layers of epitaxial single crystalline yttrium-iron garnet Y₃Fe₅O₁₂ films implanted with Si* ions with the dose of 5.10¹³ cm⁻² and energies of 100 - 150 keV using conversion electron Mossbauer spectroscopy are presented and the comparison with previously obtained results from simulations and x-ray diffractometry studies is carried out. The analysis of profiles and the integral lattice disorder in the subsurface layers confirms the validity of theoretical models used in this work.